Decentralisation of FinTech Business Models - Leal, Fátima (2022)
Digital transformation could change our daily routines, from currency to the purchases. Specifically, financial sector aims to efficiently supply distinct services using an infrastructure by relying on a centralised authority to manage and coordinate transactions at specific prices. In turn, final customers constantly seek to lower costs, quality, and reliability. Moreover, costumers desire less documentation and bureaucracy which hinder the access to financial services and credits. Financial system needs to create a digital strategy at the organisational level to address technology challenges and satisfy user’s needs. In this scenario, financial and technology domains have been integrated originating FinTech business models with significant impact. Therefore, this paper contributes not only with a technology background which allow to explore new FinTech-based business models but also describing existing business models employed in the market. Moreover, we present a comparison among traditional and FinTech-based models allowing to analyse the financial progress. The paper identifies, still, future research opportunities including regulation of decentralised financial business models.